2021
DOI: 10.1002/adem.202100130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gradient Residual Stress and Tip Shape on Stress Fields Inside Indented TiN Hard Coating

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adem.202100130.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Subsequently, other studies using the CSnanoXRD approach have been used to resolve stress field evolution in multilayered CrN coatings (Ecker et al, 2020) and CrN-AlN superlattice thin films (Todt et al, 2020) during indentation. Todt et al (2021) used in situ CSnanoXRD to investigate the effects of residual stress gradients and indenter geometry on stress field development during nanoindentation, whereas Meindlhumer et al (2021) used clamped microcantilevers to investigate the evolution of stress fields during crack growth and arrest in CrN-Cr multilayers. Importantly, it was shown that the intensity at small angles (close to the beam stop) could be used to image cracks, allowing identification of their initiation and propagation (Meindlhumer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, other studies using the CSnanoXRD approach have been used to resolve stress field evolution in multilayered CrN coatings (Ecker et al, 2020) and CrN-AlN superlattice thin films (Todt et al, 2020) during indentation. Todt et al (2021) used in situ CSnanoXRD to investigate the effects of residual stress gradients and indenter geometry on stress field development during nanoindentation, whereas Meindlhumer et al (2021) used clamped microcantilevers to investigate the evolution of stress fields during crack growth and arrest in CrN-Cr multilayers. Importantly, it was shown that the intensity at small angles (close to the beam stop) could be used to image cracks, allowing identification of their initiation and propagation (Meindlhumer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%